KARAKTERISASI SPESIFIK DAN NON SPESIFIK SIMPLISIA DAUN KAWAU (Millettia sericea) - Risa Supriningrum; Achmat Kadri Ansyori; Dewi Rahmasuari (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2020)
Empirically, kawao (Millettia sericea) leaves are used to treat fever and toothache. The development of medicinal plants into traditional medicines needs to be pursued. The first step that can be taken is characterization. Characterization is useful for knowing the quality of a simplicia, so that these results can be used as a reference for further research development. The research objective was to determine the specific and non-specific characteristics of kawao leaf simplicia. The research that was conducted was non-experimental research. The research stages included plant determination, manufacturing of simplicia, testing of specific and non-specific characteristics of simplicia. The results of the specific characterization of the macroscopic / organoleptic test showed that the leaves were elongated, dark green in color, had a distinctive smell (aromatic), bitter taste, pinnate leaf bone arrangement, tapered leaf tips, rounded leaf base, flat leaf edge, thick leaf flesh, leaf width 8 - 9.5 cm and 21 - 27 cm long. The simplicia powder is dark green, has a distinctive smell (aromatic) and has a bitter taste. Microscopic test showed that the identifier of simplicia consisted of vascular bundles, lower epidermis, anomocytic type stomata, hair covering and parenchyma. The average water soluble extract content was 35.5%, the ethanol soluble extract content was 10.5%, and the phytochemical screening results were positive for alkaloids, flavonoids, tannins, saponins and steroids. The non-specific characteristics of the water content averaged 6.75%, the total ash content was 4.28% on average, the acid insoluble ash content was 1.47% on average. Keywords: Millettia sericea leaves, specific characterization, non specific characterization